2009
DOI: 10.1016/j.jasms.2009.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Ionic matrix for matrix-enhanced surface-assisted laser desorption ionization mass spectrometry imaging (ME-SALDI-MSI)

Abstract: Matrix-enhanced surface-assisted laser desorption ionization mass spectrometry imaging (ME-SALDI MSI) has been previously demonstrated as a viable approach to improving MS imaging sensitivity. We describe here the employment of ionic matrices to replace conventional MALDI matrices as the coating layer with the aims of reducing analyte redistribution during sample preparation and improving matrix vacuum stability during imaging. In this study, CHCA/ANI (␣-cyano-4-hydroxycinnamic acid/aniline) was deposited atop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…More ionic matrixes have been tested by Lemaire et al . [55] and more recently ANI has been applied in lipid analysis [56] and whole tissue sample analysis [57]. In our hands, for MALDI-MSI of proteins in plant tissue sections, SA was the optimal matrix.…”
Section: Matrix Choice For Maldi-ms Imaging Of Proteinsmentioning
confidence: 99%
“…More ionic matrixes have been tested by Lemaire et al . [55] and more recently ANI has been applied in lipid analysis [56] and whole tissue sample analysis [57]. In our hands, for MALDI-MSI of proteins in plant tissue sections, SA was the optimal matrix.…”
Section: Matrix Choice For Maldi-ms Imaging Of Proteinsmentioning
confidence: 99%
“…Recently, curcumin(7‐bis‐(4‐hydroxy‐3‐methoxy‐phenyl)‐hepta‐1,6‐diene‐3,5‐dione), a polyphenolic compound from the plant Curcuma longa , has been revealed to be a versatile and multi‐purpose matrix for imaging lipids in skin and lung tissues . New applications mixed α‐cyano‐4‐hydroxycinnamic acid with aniline, which is basic, to produce an ionic matrix applied in lipidomics and whole tissue sample analysis .…”
Section: Ims and Maldi Imagingmentioning
confidence: 99%
“…[147][148][149][150] Liu et al demonstrated the use of a hybrid ionization approach, matrix-enhanced surface-assisted laser desorption/ionization mass spectrometry (ME-SALDI-MS), in IMS. 151,152 In ME-SALDI, the combination of MALDI with SALDI enables the successful IMS of low-mass species with improved detection sensitivity.…”
Section: Saldi-ms For Imaging Mass Spectrometrymentioning
confidence: 99%